HEALTH SERVICES COORDINATORS' UNDERSTANDING ABOUT CONTINUING EDUCATION - Maria de Lourdes Custódio Duarte; Aládia Inês de Oliveira (Universidade Federal do Paraná, 2012)
The study aimed to investigate what the health service coordinators in a municipality in the state of Rio Grande do Sul knew about continuing education. The service coordinators who participated were four nurses, one psychologist and one dentist; the data was collected through semi-structured interviews in November 2011 and was analyzed following the steps of thematic analysis. Two categories emerged from the analysis: Understanding about Continuing Education and Challenges for the implantation of the Continuing Education Policy in the municipality. It stands out that it is important for the coordinators to seek knowledge about this ministerial policy with a view to changes in the health practices in the municipality, and in the practices involved in training health professionals so as to better attend the Unified Health System's principles.KEYWORDS: